Health-Related Complications of Acromegaly—Risk of Malignant Neoplasms - Ruchala, Marek; Wolinski, Kosma (Frontiers in Endocrinology, 2019)
The issue of increased risk of benign and malignant neoplasms in patients with acromegaly remains the topic of debate from many years and was addressed by numerous studies. Many of them have shown increase in the cancer incidence. Among particular types of malignancies, thyroid, colorectal and breast cancer are most commonly indicated as associated with acromegaly. Single reports denoted increase in prevalence of neoplasms of other organs such as kidney, bone or central nervous system. Cardiovascular and respiratory tract disorders were traditionally consider as main causes of mortality in acromegalic patients, accounting for about 60% and 25% of deaths, respectively. However, according to a number of studies published over the current decade cancer became the most important cause of deaths. Aim of the current article was to review the literature concerning the risk of malignant neoplasms in acromegaly and its clinical implications.